The carbocation-catalyzed intermolecular formal [2 + 2 + 1] cycloaddition of ynamides with quinoxaline N-oxides - Jin, Hongming; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (ACS catalysis, 2019)
Carbocation-catalyzed oxidative [2 + 2 + 1] annulation of two molecules of ynamide with 2,3-dichloroquinoxaline N-oxide enables the facile and convergent assembly of fully substituted symmetric and unsymmetric furan frameworks. The quinoxaline N-oxide presented a remarkable discrepancy to common quinoline and pyridine N-oxides. A wide range of functional groups is well compatible due to the mild conditions. The strategy works also for the intramolecular macrocyclization of diynamides for the synthesis of macrocyclic furan derivatives. Moreover, a set of NMR experiments revealed the activation of a triple bond via a carbocation catalyst.
Gesehen am 13.01.2020